2020
DOI: 10.1177/0021998320941218
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bolt pretightening and preload relaxation in composite interference-fit joints under thermal effects

Abstract: The present research investigates the mechanism of bolt pretightening and preload relaxation in composite interference-fit joint structures under thermal effects. In view of the dissimilar material properties and the interfacial friction in such joints, the mechanical behavior of bolt and composites during assembly can be regarded as immediate preload response which is described by a linear elastic model, whereas the long-term behavior of composites during preload relaxation in service is considered as delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…F is the load, kis the engineering constant, and the value is 0.2. 21 The maximum static friction at the joint f c can be calculated by taking the above formula into equation (11).…”
Section: Calculations Of Spring Stiffnessesmentioning
confidence: 99%
See 1 more Smart Citation
“…F is the load, kis the engineering constant, and the value is 0.2. 21 The maximum static friction at the joint f c can be calculated by taking the above formula into equation (11).…”
Section: Calculations Of Spring Stiffnessesmentioning
confidence: 99%
“…[9][10][11] In reference,9 by establishing the theoretical model of multi-interface preload distribution, the variation of preload at nut end, between two plates and head end of the bolt in the process of preload loading was analyzed. At the same time, combined with relevant experiments and finite element simulation, the preload relaxation phenomenon under normal and thermal environment was further revealed by Hu et al, 10,11 which well explained the influence of environmental factors on the structural bearing capacity and safety. During the loading process, researchers mainly focus on the damage propagation, 12,13 strength 14 and fatigue life 15,16 under static or fatigue loads.…”
Section: Introductionmentioning
confidence: 99%
“…13 It also offers an additional safeguard to take into account the lack of ductile mechanical behavior and prevent catastrophic failure of bonded composite joints under excessive load. [14][15][16] However, composite T-joints are usually the weak link parts in composite structures. Improper design of a joint increases the possibility of structural failures or even catastrophes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, traditional riveting and bolting techniques have been extensively adopted for the bonded T‐joint structures to ensure structural integrity and meet airworthiness requirements 13 . It also offers an additional safeguard to take into account the lack of ductile mechanical behavior and prevent catastrophic failure of bonded composite joints under excessive load 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 22 identified the optimal interference-fit and torque by combing experimental and numerical methods; however, the research did not consider the impact of the preload imbalance. Hu et al 23,24 investigated the mechanism of bolt pre-tightening and preload relaxation in composite interference-fit joint structures, and identified a frictional force. This force resulted in a difference between clamping forces at two sides of the fastener.…”
Section: Introductionmentioning
confidence: 99%